Re-inventing Multimode Interference Couplers Using Subwavelength Gratings - Ortega-Moñux, Alejandro; Halir, Robert; Maese-Novo, Alejandro; Alonso-Ramos, C.; Zavargo-Peche, Luis; Pérez-Galacho, Diego; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo; Cheben, Pavel; Schmid, Jens H.; Lapointe, J.; Xu, Dan-Xia; et al. (European Physical Society, IEEE, The Optical Society, 2013)
We use the concept of subwavelength grating (SWG) refractive-index-engineering to propose and experimentally demonstrate a reduced size, slotted 2x2 MMI coupler. We also present an ultra-broadband 2x2 MMI coupler which is based on SWG dispersion engineering.
Keywords: Comunicación por fibra óptica; Silicon-Photonics; Multimode-Interference; Subwavelength-Grating; SWG; MMI-Coupler